Giant penile melanoma - S. V. Popov; I. N. Orlov; E. A. Grin; T. M. Topuzov; A. V. Tsoy; P. V. Vyazovtsev; D. Yu. Chernysheva; M. A. Kotlov (Вестник урологии, 2022)
Primary penile melanoma is an extremely rare casuistic pathology associated with a poor prognosis. The article presents a clinical case of massive lesion of the penis with malignant melanoma, and discusses surgical methods for treating this pathology.